Children’s diabetes type 1 and chronic kidney disease - O. V. Kiselnikova; L. I. Mozzhukhina; E. M. Spivak; V. V. Tuz (Лечащий Врач)
In order to identify and stratify kidney dysfunction in children in accordance with the concept of chronic kidney disease, 125 patients aged 4–18 years with type 1 diabetes mellitus were examined. The main categories were identified: albuminuria and glomerular filtration rate. A comparative analysis of the calculation of GFR by two methods — using the Schwarz formula and the level of cystatin C in the blood plasma — indicates that the latter is much more informative in children.